The start of the scientific journal ‘Fossil Record’ - Hans-Peter Schultze (Fossil Record)
This article describes the early years of the journal Fossil Record and the circumstances at the Museum für Naturkunde and the Humboldt University Berlin under which the foundation of the journal took place. The former Department of Palaeontology of the Museum für Naturkunde had a strong interest to publish its own scientific journal, and this led to the foundation of the journal in 1998 which is known today as Fossil Record. For reasons of a corporate similar appearance it was decided that the new journal as well as the two older scientific journals of the Museum für Naturkunde use the common title Mitteilungen aus dem Museum für Naturkunde in Berlin (Communications from the Museum of Natural History in Berlin) with subtitles for all three journals: Geowissenschaftliche Reihe for the palaeontological journal, Zoologische Reihe for the zoological journal and Deutsche Entomologische Zeitschrift for the entomological journal. With volume 9 (2006), the palaeontological journal appeared under the new title Fossil Record. From the beginning it was a goal of the editors to reach the international community by opening the journal to authors outside the museum and by publishing mainly in English. The palaeontological journal Fossil Record has developed from an in-house journal with international contributions to an internationally well cited journal.